Postopki za določitev požarne odpornosti prednapetih votlih plošč - Pečenko, Robert (Gradbeni vestnik, 2018)
This paper presents different procedures to determine fire safety of presstresed hollow core slab. The simplified approach is based on the method isotherm 500°C, which is given in SIST EN 1992-1-2:2005. The main part of the paper is focused on the advanced calculation method that consists of two parts. Firstly, the advanced hygro-thermal model is used to determine the temperature field in the characteristic cross-section of the concrete hollow-core slab during fire. Secondly, stress-strain state of prestressed hollow-core slab is determined based on the geometrically and materially non-linear beam model, where also slip between concrete and tendon is considered. Parametric study demonstrated that slip modelling between concrete and tendon is essential to accurately estimate the behaviour and fire resistance of prestressed hollow-core slab.
Keywords: advanced computational method; bond stress-slip; fire; napredna računska metoda; požar; prednapeta votla plošča; prestressed hollow-core slab; zdrs med kabli in betonom